National Medical Expenditure Survey, 1987: Ambulatory Medical Visit Data (Public Use Tape 14.5) ([Verlag nicht ermittelbar], 1993)
The 1987 NMES provides information on health expenditures by or on behalf of families and individuals, the financing of these expenditures, and each person's use of services. Public Use Tape 14.5 provides three data files containing information on the use of and expenditures for ambulatory medical services reported in the Household Survey. The Household Survey is one of the three major components of the 1987 National Medical Expenditure Survey (NMES). (The other two components are the Survey of American Indians and Alaska Natives [SAIAN] and the Institutional Population Component.) The Household Survey was fielded over four rounds of personal and telephone interviews at four-month intervals. Baseline data on household composition, employment, and insurance characteristics were updated each quarter, and information on all uses of and expenditures for health care services and sources of payment was obtained. An ambulatory visit is defined as a single contact with a medical provider for one or more services in either a hospital outpatient department or emergency room, a setting other than an inpatient hospital (such as a physician's office, a clinic, or a lab), a nursing home, or a person's home. The first file includes visits and telephone calls to physicians' offices (including HMOs and health departments) in settings other than a hospital or at home, and to providers of care (e.g., chiropractors and psychologists). The second file includes visits to hospital outpatient departments, and the third file covers visits to hospital emergency rooms, both regardless of provider type. A record on any of these data files represents a unique ambulatory visit. In addition, each file contains demographic information such as age, sex, and race, dates of visits, medical conditions associated with the visit, and variables such as types of procedures performed and the main reason for the visit.